PENGARUH PENAMBAHAN EKSTRAK KUNYIT (Curcuma domestica Val.) PADA PAKAN TERHADAP PERTUMBUHAN IKAN NILA (Oreo chromis niloticus) - Agnita Prihandini; Muhimatul Umami (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2022)
In the cultivation of tilapia (Oreochromis niloticus), there are still some obstacles or obstacles that farmers complain about, one of which is the high price of commercial feed, because one of the most important factors in cultivation is quality feed. Fish growth will increase if the feed given can be digested properly by fish so that the energy obtained by fish from feed can be utilized optimally. Therefore, with the background of some of the problems above, it is necessary to add natural feed in tilapia cultivation, with a nutritional composition that is in accordance with the needs of fish, this study was conducted with the aim of knowing the effect of adding natural feed in the form of turmeric extract as an immunostimulant that can trigger the growth of tilapia, as well as to determine the effect of differences in the concentration of turmeric extract added to each tilapia feed on the growth rate (weight and body length) of tilapia. This research was conducted through an experimental method, where the treatment given was in the form of adding turmeric extract with different concentrations to the artificial feed of tilapia. The results of this study proved that the higher the dose of turmeric extract added to the feed, the higher the growth rate of body length and weight of the tilapia. This is due to the balance of protein, and has the main content in the rhizome, namely essential oils and curcumin which can increase appetite, and also acts as an antioxidant.